Otimização do controlador fuzzy via algoritmo PSO para gerenciamento de energia de veículo elétrico com baterias e supercapacitores - Chiconato, Bruno Roberto Ansbach (2024)
With the increasing effects of global warming and the scarcity of oil, the development of alternative transportation technologies has been accelerated. In this study, a model of an electric veh icle is proposed that uses an energy storage system composed of batteries and supercapacitors, managed by a fuzzy controller. However, the optimal energy distribution of the system is challenging for the fuzzy controller. Therefore, a particle swarm optimization (PSO) algorithm is developed to find the ideal membership functions of the system. The PSO algorithm is a computational method that optimizes a problem by means interatively, in order to improve a candidate solution. We conduct simulations in the Google Colab environment using the python programming language. Comparing the non-optimized fuzzy controller with the optimized fuzzy controller, the results indicate that the latter presented significantly better energy distribution.